The CD14 C-159T polymorphism is not associated with asthma or asthma severity in an Australian adult population. Issue 3 (1st March 2005) - Kedda, M-A; Lose, F; Duffy, D; Bell, E; Thompson, P J; Upham, J
Abstract : Background: CD14 functions as a multifunctional receptor for bacterial cell wall components including endotoxin and lipopolysaccharide and is likely to play a role in the polarisation of T lymphocytes into Th1 and Th2 subsets, thereby influencing the cytokine profile and subsequent IgE production in response to antigen/allergen contact in allergic phenotypes. A functional C-159T polymorphism has been described in the promoter region of the gene and has been associated with increased gene expression, atopy, and non-atopic asthma in different ethnic populations. A study was undertaken to examine the association between the C-159T polymorphism and asthma, asthma severity, and atopy in a large Australian white population. Methods: PCR-RFLP analysis was used to characterise the C-159T polymorphism in mild (n = 264), moderate (n = 225) and severe (n = 79) asthmatic patients and non-asthmatic controls (n = 443), including atopic (n = 688) and non-atopic (n = 323) individuals. Association analyses were performed using χ 2 tests. Results: There was no association between the polymorphism and asthma (p = 0.468) or asthma severity (p = 0.727), and only a very weak association with atopy (p = 0.084). A meta-analysis of all studies conducted to date revealed similar genotypic frequencies in white ethnic populations and confirmed that there was no overall association with atopy (p = 0.52) or asthma (p = 0.23), although there was significant between study heterogeneity (p = 0.01). Conclusions: This study confirms that there is no association between the CD14 C-159T polymorphism and asthma or asthma severity and a weak association between this polymorphism and atopy in an adult population.